(untitled) (SCIÉNDO INGENIUM, 2026)
The objective of this research was to demonstrate the impact of applying the Problem-Based Learning (PBL) methodology on the academic performance of students in the Technological Research course of the Technical Nursing program at the Mariano Iberico Rodríguez Technological Institute in Cajamarca, 2018. Based on the theory of action learning and collaboration, the research was conducted with a sample population of 45 students divided into two teams: an experimental team of 25 students and a control team of 20. A mixed quasi-experimental methodology was used, with pre-tests and post-tests. The data was analyzed using the student’s t-test to examine small samples, leading to the following conclusion: the application of PBL to the experimental team improved their academic performance and fostered positive attitudes and skills compared to the control team. The contribution to knowledge lies in demonstrating that the application of PBL contributes to comprehensive training for future professionals.